Nuclear resonance fluorescence drug inspection - Haoyang Lan (Nature Portfolio, 2021)
Abstract There is an increasing challenge to prevent illicit drug smuggling across borders and seaports. However, the existing techniques in-and-of-themselves are not sufficient to identify the illicit drugs rapidly and accurately. In the present study, combining nuclear resonance fluorescence (NRF) spectroscopy and the element (or isotope) ratio approach, we present a novel inspection method that can simultaneously reveal the elemental (or isotopic) composition of the illicit drugs, such as widely abused methamphetamine, cocaine, heroin, ketamine and morphine. In the NRF spectroscopy, the nuclei are excited by the induced photon beam, and measurement of the characteristic energies of the emitted $$γ $$ γ rays from the distinct energy levels in the excited nuclei provides “fingerprints” of the interested elements in the illicit drugs. The element ratio approach is further used to identify drug elemental composition in principle. Monte Carlo simulations show that four NRF peaks from the nuclei $$^{12}$$ 12 C, $$^{14}$$ 14 N and $$^{16}$$ 16 O can be detected with high significance of 7−24 $$σ $$ σ using an induced photon beam flux of $$10^{11}$$ 10 11 . The ratio of $$^{14}N$$ 14 N / $$^{12}C$$ 12 C and/or $$^{16}O$$ 16 O / $$^{12}C$$ 12 C for illicit drugs inspected are then extracted using the element ratio approach. It is found that the present results of simulations are in good agreement with the theoretical calculations. The feasibility to detect the illicit drugs, inside the 15-mm-thick iron shielding, or surrounded by thin benign materials, is also discussed. It is indicated that, using the state-of-the-art $$γ $$ γ -ray source of high intensity and energy-tunability, the proposed method has a great potential for identifying drugs and explosives in a realistic measurement time.